A ROS-responsive synergistic delivery system for combined immunotherapy and chemotherapy. (March 2022) - Hu, Doudou; Zhang, Wei; Xiang, Jiajia; Li, Dongdong; Chen, Yong; Yuan, Pengcheng; Shao, Shiqun; Zhou, Zhuxian; Shen, Youqing; Tang, Jianbin
Abstract: Immune checkpoint blockade (ICB) therapies that target programmed cell death-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) pathway are currently used for the treatment of various cancer types. However, low response rates of ICB remain the major issue and limit their applications in clinic. Here, we developed a ROS-responsive synergistic delivery system (pep-PAPM@PTX) by integrating physically-encapsulated paclitaxel (PTX) and surface-modified anti-PD-L1 peptide (pep) for combined chemotherapy and ICB therapy. Pep-PAPM@PTX could bind the cell surface PD-L1 and drive its recycling to lysosomal degradation, thus reverting PTX-induced PD-L1 upregulation and downregulating PD-L1 expression. As a result, pep-PAPM@PTX significantly promoted T cell infiltration and increased tumor immunoactivating factors, synergizing PTX chemotherapy to achieve enhanced anticancer potency in a triple-negative breast cancer (TNBC) model. Graphical abstract: A ROS-responsive synergistic delivery system (pep-PAPM@PTX) was developed by integrating physically-encapsulated paclitaxel (PTX) and surface-modified anti-PD-L1 peptide (pep) for combined chemotherapy and ICB therapy. Image 1